(untitled) (Indonesian Economic Justice Review, 2024)
This paper examines Indonesia’s development goals and the pursuit of economic justice, focusing on the intersection of sustainable development and inclusive growth. Despite impressive economic growth over the past few decades, Indonesia faces significant challenges in ensuring that the benefits of development reach all segments of society, particularly marginalized groups such as indigenous peoples, rural populations, and women. The study critically analyzes Indonesia’s National Medium-Term Development Plan (RPJMN) and its alignment with the United Nations’ Sustainable Development Goals (SDGs), specifically in terms of reducing poverty, promoting equitable economic opportunities, and enhancing social mobility. The paper highlights the tension between rapid economic growth and the need for social justice, especially as inequality, environmental degradation, and social exclusion continue to persist. By assessing key policies such as social protection programs, rural development initiatives, and infrastructure projects, the paper evaluates how well Indonesia’s development strategy incorporates economic justice principles. The findings suggest that while there are efforts to integrate sustainability and equity into development plans, more targeted measures are needed to address structural inequalities. The paper concludes with policy recommendations that emphasize the importance of inclusive growth, equitable resource distribution, and the active involvement of marginalized communities in the development process.